Two new species of the genus Cyana Walker, 1854 from China (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; Huang, Si-Yao; Saldaitis, Aidas (Zootaxa, 2021)
Two new species of Cyana Walker, 1854 are described: Cyana fascioloides S.-Y. Huang, Volynkin & Saldaitis, sp. n. from Guangxi and Cyana longmena Volynkin, S.-Y. Huang & Saldaitis, sp. n. from Sichuan. These species are diagnosed from Cyana fasciola (Elwes, 1890) and Cyana fukiensis (Daniel, 1953). Adults together with male and female genitalia of the new and similar species are illustrated.